Análise da substituição parcial do cimento portland por micro sílica na produção de concreto - Silva, Ilg Patrick Dantas (Universidade Federal Rural do Semi-Árido, 2018)
The advancement of technological development in the construction industry is always related to the use of quality materials, for increasing the durability of structures and that has easy workability. In this context, the present work aims at analyzing the use of active silica in various proportions with the purpose of achieving a quality concrete and that can also reduce the consumption of Portland cement. The experimental methodology was divided into two stages: at first stage, it was made a study of the aggregates properties, and the second, concrete mixtures with substitution were confectioned in the proportions of substitution of cement Portland in 20%, 30% and 40%. The results indicate that the trace containing 20% of microsilica stood out for presenting an equality of resistance. From these results, it is concluded that the micro silica may be an alternate material to use.
Artigo Acadêmico
Keywords: Construção civil; Durabilidade; Pozolana; ENGENHARIAS::ENGENHARIA CIVIL